Pengaruh Corporate Social Responsibility Terhadap Kinerja Keuangan - Lestari, Nanik; Lelyta, Novi (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2019)
This research aims to obtain empirical evidence on the influence of Corporate Social Responsibility impact on Corporate Financial Performance. Data used are non-financial companies in Indonesia Stock Exchange (IDX) period 2010-2015 as many as 419 samples. Corporate Financial Performance dependent variable is measured by Return on Asset (ROA) and Retunr on Invesment Capital (ROIC).The Independent variables of corporate Social Responsibility is adopted from the Global Reporting Initiative (GRI) G3.1 Guidelines with 6 indicators and 81 items. The control variables is Sales Growth. Data analysis technique used is panel data regression analysis. The results of this study are, the first Corporate Social Responsibility has positive on Corporate Financial Performance proxicated by ROA. The second, Corporate Social Responsibility has positive on Corporate Financial Performance proxicated by ROIC.